Microelectrode Sensor for Real-Time Measurements of Nitrite in the Living Brain, in the Presence of Ascorbate - Tiago Monteiro; Cândida Dias; Cátia F. Lourenço; Ana Ledo; Rui M. Barbosa; M. Gabriela Almeida (Biosensors, 2021)
The impaired blood flow to the brain causes a decrease in the supply of oxygen that can result in cerebral ischemia; if the blood flow is not restored quickly, neuronal injury or death will occur. Under hypoxic conditions, the production of nitric oxide (●NO), via the classical L-arginine–●NO synthase pathway, is reduced, which can compromise ●NO-dependent vasodilation. However, the alternative nitrite (NO2−) reduction to ●NO, under neuronal hypoxia and ischemia conditions, has been viewed as an in vivo storage pool of ●NO, complementing its enzymatic synthesis. Brain research is thus demanding suitable tools to probe nitrite’s temporal and spatial dynamics in vivo. In this work, we propose a new method for the real-time measurement of nitrite concentration in the brain extracellular space, using fast-scan cyclic voltammetry (FSCV) and carbon microfiber electrodes as sensing probes. In this way, nitrite was detected anodically and in vitro, in the 5–500 µM range, in the presence of increasing physiological concentrations of ascorbate (100–500 µM). These sensors were then tested for real-time and in vivo recordings in the anesthetized rat hippocampus; using fast electrochemical techniques, local and reproducible transients of nitrite oxidation signals were observed, upon pressure ejection of an exogenous nitrite solution into the brain tissue. Nitrite microsensors are thus a valuable tool for investigating the role of this inorganic anion in brain redox signaling.